Surgical complications of cochlear implantation in a tertiary university hospital. (4th March 2018) - Awad, Al Hussein; Rashad, Usama M.; Gamal, Nihal; Youssif, Mostafa A.
Abstract : Introduction: Cochlear implantation remains a popular and effective therapy for patients with sensorineural hearing loss that not get benefit from conventional hearing aids Objective: To analyze the surgical complications obtained in patients that underwent cochlear implantation in a tertiary university hospital. Materials and methods: Retrospective analysis of the medical files of cochlear implant patients who underwent surgery at our institution between October 2014 and July 2016. This population comprised 163 patients (52.7% males and 47.3% females). Complications were classified in to 'major' and 'minor' complications depending on degree of management. Results: Overall, the mean age at the time of implantation was 7.44 years. The cause of deafness was congenital in 81.6% of patients and acquired in 18.4% of patients. The overall complication rate was 10.43%, 3.68% being major and 6.75% being minor complications. The most common minor complication in our series was wound complications, and the most common major complication was device failure. Excluding device failures, the major complication rate was 1.84%. Conclusion: Cochlear implantation is a safe surgical technique for rehabilitation of patients with severe to profound hearing loss, associated with a low surgical complications rate. The majority of surgical complications can be managed with conservative measures or minimal intervention.